STUDI PENGARUH DOPING NA2SO4 DAN NA2CO3 TERHADAP FOTOKONDUKTIVITAS POLI (N- VINIL KARBAZOL) - (NIM : 20295005), Aminatun
Abstract : It was done photoconductivity observation of poly (N- Vinyl Carbazole) or PVK by giving continue radiation repeatedly. The generation and recombination process of charge carrier in PVK showed transient phenomena in photocurrent. By doping treatment of Na2SO4 and Na2CO3 was obtained increasing of photoconductivity. Doping treatment of the same concentration of Na2SO4gave the higher photoconductivity than Na2CO3 doping. The variation of doping concentration showed a change of photoconductivity value. The doping concentration of 10% mol gave higher photoconductivity value than the lower concentration. Beside photoconductivity value, it was also accounted the lifetime of the whole sample. It was obtained that the lifetime increase with increasing photocurrent.